Free-living marine nematodes of Desmodorella and Zalonema (Nematoda: Desmodoridae) with description of two new species from the deep sea of the North Western Pacific - Fadeeva, Natalia; Mordukhovich, Vladimir; Zograf, Julia (Zootaxa, 2016)
Examination of material recently collected by the German-Russian deep-sea expeditions has revealed that new species occur regularly in macro- and meiobenthic samples of the North-Western (NW) Pacific. In this paper, we report three desmodorid species of the genera Desmodorella and Zalonema from the NW Pacific. They were studied and described using both scanning electron microscopy (SEM) and light microscopy. Desmodorella tenuispiculum (Allgen, 1928) was found at several locations in the Sea of Japan during the Russian-German expedition SoJaBio (Sea of Japan Biodiversity Studies) cruise of RV ''Akademik M.V. Lavrentyev'' in 2010, at water depths ranging between 515 and 1500 m. Zalonema granda sp. nov. and Z. kamchatkaensis sp. nov. are characterized by having a larger body size in comparison with other species of the genus. Zalonema kamchatkaensis sp. nov. is characterized by having a convex cephalic capsule, subcephalic setae (3–4 μm long) located in the middle and at the posterior region of the cephalic capsule, very large spiral amphidial fovea with 2.1–2.2 turns, sexual dimorphism in amphideal fovea size (larger in males, 39–45 μm, than in females, 37–43 μm). Zalonema granda sp. nov. is characterized by having a very long body (3.3–4.3 mm), curved elongate spicules (1.4–1.6 body diameter long), with blade broadening anteriorly towards the rounded capitulum, and pointed distally; weakly developed tubular gubernaculum, and absence of pre-cloacal supplements.